PERFORMANCE ANALYSIS OF ELECTROCHEMICAL GAS SENSOR FOR NITROGEN DIOXIDE (NO2) IN LABORATORY AND FIELD SCALE WITH STATISTICAL CORRELATION ANALYSIS METHOD - Anisa Muthia, Hasna
NO2 is one kind of toxic gas. Monitoring NO2 concentration in ambient air needed, to know that level concentration. Currently, the big problem in air quality monitoring system is about cost. New technology electrochemical sensors with low cost investment and operation is interested to develop. Electrochemical gas sensors that was tested type NO2-B42F had passive sampling methods and automatically analysis methods every 2-3 minutes. This research wanted to know performance electrochemical sensors by knowing accuracy and precision value from validation in laboratory test and data verification in field test. Laboratory test has been done by using variation concentration gas standard NO2 there were limit value (0 ppm), upper assessment threshold (0.197 ppm), and critical value (1.173 ppm) reference method in laboratory test was Griess Saltzman. In collocation test electrochemical sensors tested at Bundaran HI and Lubang Buaya monitoring stations. Reference method that was used in field test was chemiluminescence on Horiba NOx Analyzer instrument type APNA-370. Data analysis was done by using statistic correlation method. Result of laboratory test of sensors read was 0.6132 times from the standar method Griess Saltzman and average precision value was 98.7%. The level of accuracy for 79,4% data was not approptiate the standards. Result of field test at Bundaran HI average precision value was 96.177% and for collocation at Lubang Buaya was 97,651%. According to this result for sensor in 1 year 8 months operating time, performance sensor was not accurate and precision to measure NO2 concentration. According to field test result, meteorological parameter temperature, relative humidity and wind speed affect sensor performance in term of accuracy.